Potential of Ecology based Agrotourism for Agricultural Education in Besur Village, Lamongan Regency - Slamet Ifandi; Yustika Aulia Rahma (Biosaintifika: Journal of Biology & Biology Education, 2020)
Currently, agriculture has prospective potential to be developed as a tourist attraction, one of which is agricultural tourism with an ecological perspective. The objective of the research was to examine the potential of ecology-based agrotourism as a means for agricultural education in Besur Village, Lamongan Regency. The research applied a quantitative descriptive approach in the form of scoring, weighting, and ranking of the categories being assessed. The research data consisted of primary and secondary data. The data was collected using direct observation and in-depth interviews. The data analysis was carried out using for the feasibility ofÂ  agrotourism area. The results showed that the area of Besur Village was classified as suitable (potential) with zone I that had the highest KKA value (2.6) as the object of the agrotourism. Potential ecological aspects obtained analysis 36 species of food producing plants. The highest Importance Value Index (IVI) of plant species was Â recorded for Oryza sativa spp. (83.76%) and Zea mays L. (27.11%). Analysis of the physico-chemical properties of soil resulted in moderate or sufficient fertility. Analysis of public perceptions obtained was 4.08 and classified as good for the development of agrotourism in Besur Village. The novelty of this research was to obtain of the potential for agrotourism management in Besur Village through an ecological approach based on the concept of Healthy Plant Management.